2014
DOI: 10.1111/papr.12228
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Greater Occipital Nerve Block for Cervicogenic Headache: Comparing Classical and Subcompartmental Techniques

Abstract: While the classical technique for GON block resulted in only 2 weeks of analgesia, the subcompartmental technique resulted in at least 24 weeks of analgesia, being 5 mL volume sufficient for the performance of the block under fluoroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 18 publications
(33 reference statements)
0
31
0
2
Order By: Relevance
“…Injection by using an anatomic landmark-based approach is the most commonly performed technique that involves injecting medication at the level of the superior nuchal line, medial to the palpated occipital artery 17. Fluoroscopic guidance has also been used to identify the pertinent bony landmarks in an attempt to improve accuracy 18. Using a palpation- or fluoroscopy-based technique often requires injection of greater volumes of local anesthetic, which increases the risk of unintentionally blocking adjacent nerves (lesser occipital nerve, third occipital nerve), and therefore limiting the diagnostic utility of the injection.…”
Section: Introductionmentioning
confidence: 99%
“…Injection by using an anatomic landmark-based approach is the most commonly performed technique that involves injecting medication at the level of the superior nuchal line, medial to the palpated occipital artery 17. Fluoroscopic guidance has also been used to identify the pertinent bony landmarks in an attempt to improve accuracy 18. Using a palpation- or fluoroscopy-based technique often requires injection of greater volumes of local anesthetic, which increases the risk of unintentionally blocking adjacent nerves (lesser occipital nerve, third occipital nerve), and therefore limiting the diagnostic utility of the injection.…”
Section: Introductionmentioning
confidence: 99%
“…6 Moreover, GON blocks have shown efficacy in the diagnosis and treatment of cervicogenic headache. [7][8][9] Many practitioners perform GON injections using a conventional approach, relying solely on superficial bone-based anatomic landmarks to infiltrate local anesthetic and corticosteroid around the nerve at the level of the superior nuchal line. Some clinicians also use fluoroscopy to confirm the location of bony landmarks.…”
mentioning
confidence: 99%
“…Some clinicians also use fluoroscopy to confirm the location of bony landmarks. 7 The ambiguity of these injections poses a risk of anesthetizing adjacent structures or injecting into vessels, such as the occipital artery. 5 Very limited research has been done to quantify the risk of these injections, but a complication rate of 5% to 10% has been reported, including headache, dizziness, blurred vision, and syncope.…”
mentioning
confidence: 99%
“…The benefits of physical treatments, cervical epidural steroid injections, and botulinum toxin for the treatment of CH have been reported previously (13,14,15). Prior studies relating to the treatment of CH have shown that local steroid injection for CH are effective (6,7,8,16). Despite the fact that injection of steroid in the GON is a valid and less destructive interventional treatment option, definitive evidence is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies including different types of study designs reported an improved control of CH pain after GON blocks (6,7,8). To date, however, there are no similarly well-known GON injection protocols for the treatment of CH.…”
Section: Introductionmentioning
confidence: 99%